Building Patient Loyalty Through Location and Quality Services with Patient Satisfaction as a Variable Intervening (Case Study at the Widya Dharma Husada Clinic in Pamulang South Tangerang City) - Ahidin, Udin; Kasmad, Kasmad; Ramadhan, Rizky (International Journal of Psychology and Health Science, 2023)
The aim of this research is to understand the influence of location and service quality on patient loyalty at the Widya Dharma Husada Clinic with patient satisfaction as an intervening variable. The method used is quantitative. The sampling technique used saturated sampling/Slovin's formula and a sample of 100 respondents was obtained. Data analysis carried out included: validity test, reliability test, classical assumption test, linear regression analysis, coefficient of determination test, path test, sobel test, and hypothesis test. The results of this research are that location has a positive and significant effect on patient satisfaction. Service quality has a positive and significant effect on patient satisfaction. Location and quality of service simultaneously have a positive and significant effect on patient satisfaction. Location has a positive and significant effect on loyalty. Service quality has a positive and significant effect on loyalty. Patient satisfaction has a positive and significant effect on loyalty. Location, service quality and patient satisfaction simultaneously have a positive and significant effect on loyalty. Patient satisfaction is able to mediate the influence of location on patient loyalty. Patient satisfaction is able to mediate the influence of service quality on patient loyalty.